New record of the genus Biscogniauxia (Xylariaceae) from Vietnam - Que, Do Duc; Lam, Duong Minh; Hao, Vuong Trong (Academia Journal of Biology, 2013)
The genus Biscogniauxia comprises 57 species known and is the 5th genus in terms of species number of the family Xylariaceae. The genus Biscogniauxia is found in different areas of the world but mostly found in the tropics. Based on the analysis of samples collected in Cuc Phuong National Park, Ninh Binh province and in Muong Phang primary forest, Dien Bien province, we found two species, namely B. Philippinensis and B. uniapiculata. This is the new record of genus Biscogniauxia for Vietnam’s flora. Thus there are 12 genera of the family Xylariaceae known from Vietnam among 74 genera of the world’s flora. This paper provided a key to species of the genus Biscogniauxia from Vietnam and some close related species known. The detail redescriptions of the two species are also given.